Smart wireless sensor node for impedance- based SHM applications with multi-sensor capability and automatic compensation for temperature effects - Cortez, Nicolás E. [UNESP]; Filho, Jozué Vieira [UNESP]; Baptista, Fabricio G. [UNESP] (My University, 2015)
This paper presents a smart wireless sensor node for wireless structural health monitoring systems based on a simple method to detect damage in structures using the electromechanical impedance technique. The proposed smart wireless sensor node is a portable and autonomous core based on microcontroller and digital synthesizer supporting multiple sensors, which automatically performs the compensation of the measurements due to ambient temperature variation and can be monitored through either a network ZigBee or a network GSM/GPRS. The identification of damage is performed by simply analyzing the variations of root main square (RMS) voltage of the response signals from piezoelectric transducers, such as PZT (Pb-lead Zirconate Titanate) patches bonded to the structure, obtained for different frequencies of excitation signals in time domain. The temperature compensation is performed using the correlation coefficients to compute the optimal frequency displacement value from the data signatures. The proposed system was built and experiments were successfully performed on an aluminum structure and temperature varying from 0 to 60C. The results indicate that the proposed smart wireless sensor node, which can be controlled from worldwide, is able to detect damage in the incipient stage, even with the presence of significant temperature variation.